Extended Fundamental Diagrams. Issue 4 (April 2020) - Wagner, Peter; Nippold, Ronald; Grötsch, Johannes
By using a large data-base of single vehicle data from a German freeway, the fundamental diagram (FD) can be extended. These types of data allow extraction of additional information that can be displayed as a function of the traffic flowQ and speedV . This is demonstrated here with a surrogate measure of safety (SMoS) and two other indices, which can be used to perform more in-depth analyses of traffic flow. In the case of the SMoS, it is possible to identify more and less dangerous regions in the extended FD.